Réponses

Meilleure réponse !
2012-09-22T21:43:21+02:00

A)  (x-2)*(4x-1)+(1-4x)*(x+2)

= 4x² - x - 8x +2 + x + 2 - 4x² - 8x

= - 16x + 4

 

B)  (x+2)²-(2x+3)²

= x² + 4x + 4 - 4x² - 12x - 9

= -3x² - 8x -5

 

C)  x(2x-1)(-x+3)

= -2x^3 + 6x² + x² - 3x 

= -2x^3 + 7x² - 3x

 

D)  (7-2x)(7+2x)-(7+2x)²+(7-2x)²

= 49 + 14x - 14x - 4x² - 49 - 28x - 4x² + 49 - 28x + 4x²

= 49 - 4x² - 28x  - 28x

=  - 4x² - 56x+ 49

2012-09-22T23:34:16+02:00

A=(x-2)*(4x-1)+(1-4x)*(x+2)

A=4x²-x-8x+2+x+2-4x²-8x

A= -16x + 4


B=(x+2)²-(2x+3)²   <- identité remarquable de la forme A² - B²

B= (x+2-2x-3)(x+2+2x+3)

B= (-x-1)(3x+5)

B= -3x²-5x-3x-5

B= -3x²-8x-5


C= x(2x-1)(-x+3)

C= -2x^3 + 6x² + x² - 3x 

C= -2x^3 + 7x² - 3x

 

D= (7-2x)(7+2x)-(7+2x)²+(7-2x)²

D= 49 + 14x - 14x - 4x² - 49 - 28x - 4x² + 49 - 28x + 4x²

D= 49 - 4x² - 28x  - 28x

D=  - 4x² - 56x+ 49